2021
DOI: 10.24857/rgsa.v14i2.2162
|View full text |Cite
|
Sign up to set email alerts
|

Influência da Identidade Étnica na Percepção de Justiça Organizacional Mediada pelo Sistema de Recompensas

Abstract: Este estudo analisa a relação entre a identidade étnica e a percepção de justiça organizacional mediada pelo sistema de recompensas. A identidade étnica foi analisada pela caracterização étnica dos respondentes, dos pais e do sentimento de pertencimento étnico. Para o construto, percepção de justiça organizacional, consideraram-se as dimensões de justiça distributiva, processual, informacional e interpessoal. Uma survey foi realizada com funcionários de uma organização multiétnica, do Ministério das Relações E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another variable that has been shown to influence the behavior of individuals is the feeling of justice. Issifou and Beuren's (2020) study revealed that the theoretical implications on ethnic, that sense of justice contributes to explaining distributive, procedural, informational and interpersonal perceptions.…”
Section: The Concept Of Self-deceptionmentioning
confidence: 89%
“…Another variable that has been shown to influence the behavior of individuals is the feeling of justice. Issifou and Beuren's (2020) study revealed that the theoretical implications on ethnic, that sense of justice contributes to explaining distributive, procedural, informational and interpersonal perceptions.…”
Section: The Concept Of Self-deceptionmentioning
confidence: 89%
“…This suggests that other variables may interfere in this relationship, which prompts the inclusion of other variables in the theoretical model of the research. It is also possible that the perception of organizational justice is impacted by antecedent or consequent variables, as in the study by Issifou and Beuren (2021), in which ethnic identification and the reward system contributed to explaining the perception of organizational justice.…”
Section: Andreia Dulce Martins / Larissa Dalla Corte Euzebio / Ilse M...mentioning
confidence: 99%